UNVEILING THE LINK: DOES DIGITAL MARKETING ADOPTION FUEL SUSTAINABLE GROWTH FOR SMEs IN INDONESIA? - Nuril Aulia Munawaroh; Sudarmiatin Sudarmiatin; Widya Putimelinda (Transpublika Publisher, 2024)
The research indicates that the adoption of digital marketing among SMEs in Indonesia significantly contributes to their sustainable growth. The study identifies several key factors that influence this relationship, including attitude toward digital marketing, perceived behavioral control, subjective norm, intention to use digital marketing, and actual use of digital marketing. Specifically, the study highlights that positive attitudes towards digital marketing and subjective norms directly influence the intention to use digital marketing, which subsequently impacts the actual adoption of digital marketing tools. Moreover, the study underscores that the actual use of digital marketing has a direct positive effect on the sustainable growth of SMEs. These findings affirm the potential of digital marketing as a valuable resource for enhancing the sustainable growth of SMEs in Indonesia. By comprehending the factors that drive the adoption and utilization of digital marketing, businesses can develop effective strategies to promote sustainable growth.